Smiley Shark - Galloway, Ruth, 1973- (London : Little Tiger Press, 2003)
Smiley Shark's toothy smile frightens the other sea animals but comes in handy when they are caught in a net.
2.3
K-3.
K-3
Keywords: Marine animals -- Fiction; Sharks -- Fiction; Smiling -- Fiction; Marine animals -- Fiction; Sharks -- Fiction; Smiling -- Fiction